Globalizacja a wartościowanie — na przykładzie Literackiej Nagrody „Angelus” - Rutkiewicz, Paweł Krzysztof (Studia Etnologiczne i Antropologiczne, 2014)
The main purpose of the article is to consider the institution of literary award as something, which could consolidate a culture in spite of globalization — understood as a set of processes causing the cultural destabilization. The article is focused on literary texts honored with Angelus Central European Award (from a year 2006 to 2012). The following interpretations are used for exegesis of esthetical and ethical values, which are expected to form a kind of symbolical basis for the socio-cultural space of Central Europe.